Restorative Treatment of Amelogenesis Imperfecta with Prefabricated Composite Veneers - Claudio Novelli; Maurizio Pascadopoli; Andrea Scribante (Case Reports in Dentistry)
This case report presents the use of prefabricated composite veneers for restorative treatment of amelogenesis imperfecta (AI). This technique bridges the gap between a conventional direct technique and a conventional indirect technique and introduces an alternative semidirect restorative technique for AI patients. The aim of this case report is to describe restoration of a young girl with severe AI using prefabricated composite veneers and to discuss the benefits and limitations of this technique compared to the alternative restorative techniques.